2016
DOI: 10.1186/s13568-016-0239-3
|View full text |Cite
|
Sign up to set email alerts
|

Multi-trait QTL analysis for agronomic and quality characters of Agaricus bisporus (button mushrooms)

Abstract: The demand for button mushrooms of high quality is increasing. Superior button mushroom varieties require the combination of multiple traits to maximize productivity and quality. Very often these traits are correlated and should, therefore, be evaluated together rather than as single traits. In order to unravel the genetic architecture of multiple traits of Agaricus bisporus and the genetic correlations among traits, we have investigated a total of six agronomic and quality traits through multi-trait QTL analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Thus, an account of the genetic architecture of a trait based on a single population likely describes only a small proportion of all the loci, their effects, and potential interactions that contribute to the intraspecific phenotypic variation for a trait 17,20 . Similarly, QTL analysis involving multiple traits allows for the decomposition of genetic bases of within trait variations as well as correlations among traits in terms of the signs and magnitudes of QTL effects 21 . To this end, the use of two or more segregating mapping populations with two or more measured traits in a single study have become common 20,22,23 .…”
mentioning
confidence: 99%
“…Thus, an account of the genetic architecture of a trait based on a single population likely describes only a small proportion of all the loci, their effects, and potential interactions that contribute to the intraspecific phenotypic variation for a trait 17,20 . Similarly, QTL analysis involving multiple traits allows for the decomposition of genetic bases of within trait variations as well as correlations among traits in terms of the signs and magnitudes of QTL effects 21 . To this end, the use of two or more segregating mapping populations with two or more measured traits in a single study have become common 20,22,23 .…”
mentioning
confidence: 99%
“…Foulongne-Oriol et al ( 2009 ) demonstrated that microsatellite markers were more powerful to generate linkage maps for A. bisporus . Since the publication of the whole genome sequence of the button mushroom (Morin et al 2012 ; Sonnenberg et al 2016 ), SNP markers can be used and they appear to be very useful in generating linkage maps (Gao et al 2016 , 2015 ) and for precise location of meiotic crossovers (Sonnenberg et al 2016 ).…”
Section: Genetic Markers and Genetic Dissection Of Traitsmentioning
confidence: 99%
“…50% of the variation. Gao et al ( 2016 ) also analysed the quality traits with five additional agronomic traits through multi-trait QTL analyses in a mixed model. Major and minor QTL were detected for the trait earliness (first day picking), firmness, cap color, compost colonisation and scaling of mushroom caps.…”
Section: Genetic Markers and Genetic Dissection Of Traitsmentioning
confidence: 99%
See 2 more Smart Citations